Calculation of vibrational SFG spectra from molecular dynamics simulations - Musil, Patrik (Jihočeská univerzita, 2022)
In this thesis, implementation of calculation vibrational Sum-Frequency Generation (SFG) spectra from classical molecular simulations of aqueous solutions in the O-H vibrations region is presented. The key part of the thesis was significant improvement of the original codes used by the group of Prof. Marie-Pierre Gaigeot to post-process ab initio molecular dynamics trajectories to predict vibrational SFG spectra and apply it to classical molecular dynamics simulations. Particular attention was paid to modifying and optimizing the code for processing much larger systems (number of molecules) and much longer trajectories (longer simulation times), allowing to take advantage of classical simulations to work on larges scales than the ab initio simulations. The code also integrates calculations of contributions from water O-H bonds and surface hydroxyls. As a new feature, calculation of cross-correlations among molecules was implemented. The performance of the resulting codes is verified and the influence of classical molecular simulation parameters, as well as parameters entering the SFG spectra calculations, on the calculated vibrational SFG spectra is studied for fluorite/water interface.
Calculation of vibrational SFG spectra from molecular dynamics simulations
Keywords: computer simulations; solid-liquid interface; nonlinear optics; sum-frequency generation; spectroscopy; computer simulations; solid-liquid interface; nonlinear optics; sum-frequency generation; spectroscopy